Proportion of TLR-9 Gene Polymorphisms at rs352139 (G1174A) in HIV/AIDS Patients in West Java, Indonesia - Yehezkiel Yonathan; Edhyana Sahiratmadja; Agnes Rengga Indrati (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Human immunodeficiency virus (HIV) infection is the main cause of the immunodeficiency syndrome (AIDS). TLR-9 gene encodes a toll-like receptor-9 that plays a key role in innate immunity. This study aimed to describe the proportion of TLR-9 polymorphisms at rs352139 in patients with human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) in Bandung, West Java, Indonesia.Methods: This was a descriptive study involving a total of 96 patients with HIV/AIDS treated in a tertiary hospital in Bandung, West Java, Indonesia in 2013. TLR-9 gene polymorphisms at rs 352139 were examined using a mass screening platform and the genotypes proportion was presented in percentage and compared with other populations.Results: The average age of the HIV/AIDS patients recruited was 30 years (SD+6.1) and the baseline mean of CD4+ count was 318.02 mm3 (Normal was 1,500 mm3) (SD+273.1). The proportion of polymorphisms at rs352139or G1174A presented a wild type genotype GG (42.7%), GA (44.9%), and AA (12.4%), resulting in a total proportion nucleotide change of 57.3%.Conclusion: A total proportion of nucleotide change or polymorphisms is higher than the wild type. A further cohort study is of great interest to associate the rs352139 polymorphisms with a decrease in CD4+cells in HIV/AIDS patients, confirming a rapid disease progression.